Annealing-induced changes in wear resistance and nanomechanical properties of CuZr metallic glass thin films - Jianjing Gao; Nana He; Athota Rathan; Manoj Kumar Agrawal; Harsha Mohanty (Materials Research Express, 2023)
Over recent years, metallic glass thin films (MGTFs) have found extensive applications in advanced micro-engineering systems. Consequently, there is a need to thoroughly assess the nanomechanical and tribological behaviors of MGTFs to optimize the design of efficient components. In this study, we employed the nanoindentation technique in various modes to investigate the elastic heterogeneity, tribological response, and mechanical properties of CuZr amorphous films. Before conducting the mechanical tests, annealing treatments at 500 K and 600 K were performed to create samples with different stored energies. The thermal history analysis revealed that the annealing process reduced the stored energy in the microstructure. Furthermore, the pre-annealing treatment resulted in increased hardness and Young’s modulus of the thin films. Additionally, higher annealing temperatures significantly improved the wear resistance of the MGTFs. Observing the serration dynamics in the scratching test, we noticed that the annealing treatment induced larger shear bands on the wear track side. Moreover, the increase in annealing temperature led to a reduction in elastic heterogeneity, which was consistent with the enthalpy relaxation values in the samples. This suggests that the annealing temperature enhanced the densely packed atomic structure, leading to the stabilization of the thin films.